Does Your Cohort Matter? Measuring Peer Effects in College Achievement - Carrell, Scott E.; Fullerton, Richard L.; West, James E. (Journal of Labor Economics, 2009)
We estimate peer effects in college achievement using a data set in which individuals are exogenously assigned to peer groups of about 30 students with whom they are required to spend the majority of their time interacting. This feature enables us to estimate peer effects that are more comparable to changing the entire cohort of peers. Using this broad peer group, we measure academic peer effects of much larger magnitude than found in previous studies. The effects persist at a diminished rate into follow-on years, and we find evidence of nonlinearities in the magnitude of the effects across student academic ability. (c) 2009 by The University of Chicago.